Medieval clothing and textiles, Volume 16 - Wright, Monica L. 1968-; Netherton, Robin 1959-; Owen-Crocker, Gale R. 1947- (The Boydell Press, 2020)
The best new research on medieval clothing and textiles, drawing from a range of disciplines